Assessing leverage points for strengthening adaptive capacity in a Global South food system: A psychometric approach - Rosengren, Linda M.; Kaseva, Janne; Sell, Mila; Raymond, Christopher M. (Elsevier, 2024)
Despite the burgeoning literature on adaptive capacity, there is a lack of psychometric approaches for assessing the determinants of adaptive capacity, particularly in food systems in the Global South. The study addressed this knowledge gap by investigating four determinants, previously identified as leverage points, for strengthening adaptive capacity: access to finance, access to and use of information and knowledge, social learning, and gender equality. Drawing on a survey (n = 1,271) of food system actors in Kisumu County, Kenya, we conducted a confirmatory factor analysis, which yielded factors of moderate-high internal validity and reliability. We then used structural equation modelling to examine the causal effect of food system actors’ attitudes and beliefs towards the four leverage points with regards to their perceived adaptive capacity. Two factors, access to finance and social learning, were significant positive predictors of adaptive capacity. A third leverage point factor, gender equality, contributed to the respondents’ perceived adaptive capacity through the mediating factor of assets. The results reveal entry points for strategic adaptation planning and raise complexities related to gender norms and values. We discuss the implications of these findings for adaptive capacity and transformative adaptation theory in food systems in the Global South.
Keywords: Adaptive capacity; Determinants; Leverage points; Structural equation modelling; Climate change adaptation; Kenya